Microbiome-host interactions - Dhanasekaran, Dharumadurai; Paul, Dhiraj; Amaresan, N.; Sankaranarayanan, A.; Shouche, Yogesh (Boca Raton, FL CRC Press, an imprint of the Taylor & Francis Group, 2021)
"Microbiome a promising and fascinating subject in the modern Biology. It integrates the microbial communities in human, animal, plant and environment. In human, the microbiota associated with gut, skin, genital organs, oral and respiratory organs. Plant microbial community is referred as 'holobiont' exerted in maintenance and health of the plants further it influenced its role in the animal health and environment. The contents of the Microbiome and Host Interactions book covered all area and new research trends in the fields of plant, animal, human and environmental microbiomes and their interactions. This book covered the details about the microbiome in soil environment to polar (Antartic) microbiota, microbiome role in health and disease, microbiota functions in Caenorhabditis elegans, mycobiome in agroecosystem, rice root and actinorhizal root nodule microbiome, speleothems, microbiome of marine shallow water hydrothermal vents. Moreover, this book also provides a comprehensive account on advanced Next-Generation DNA sequencing, metagenomic techniques, high-throughput 16S rRNA sequencing and understand nucleic acid sequence data from fungal, algal, viral, bacterial, cyanobacterial, actinobacterial and archaeal communities using QIIME software (Quantitative Insights Into Microbial Ecology). Salient features: Summarize the recent insight in the Microbiome and host interactions in distinct habitat including antarctic, hydrothermal vents water, speleothems, oral, skin, gut, feces, reproductive tract, soil, root, root nodules, forest and mangroves. Illustrates the high-throughput amplicon sequencing, computational techniques involved in the microbiota analysis, downstream analysis and visualization, multivariate analysis commonly used for microbiome analysis. Describe the probiotics and prebiotics in the composition of the gut microbiota, skin microbiome impact in dermatologic disease prevention, microbial communities in the reproductive tract of human and animals. Information presented in a reachable way for valuable to students, teachers, researchers, microbiologists, computational biologist and other professionals who interested to strengthen and enlarge their knowledge about microbiome analysis by with Next-Generation DNA Sequencing in different branches of sciences"--Provided by publisher.
An insights of Microbiome science / Savitha, T, A. Sankaranarayanan, Ashraf Y. Z. Khalifa -- Multi-omics : overview, challenges and applications / Sushant Parab, Federico Bussolino -- Computational techniques use for microbial diversity analysis / Dattatray S. Mongad, Nikeeta S. Chavan and Yogesh S. Shouche -- Downstream analysis and Visualization - knowledge discovery - Alpha and Beta diversity / Murali Sankar Perumal and Shreedevasena Sakthibalan -- Biostatistics including multivariate analysis commonly used for microbiome analysis / Priyanka Sarkar -- Structure and functional role of microbiome associated with specific organs of healthy individuals / Shanmugaraj Gowrishankar, Arumugam Kamaladevi and Shunmugiah Karutha Pandian -- Structure and function of healthy human microbiome : Role in health and disease / Sunil Banskar and Shrikant Bhute -- Human microbiome's role in disease / Sahab Ram and Yogesh Shouche -- Role of human gut microbiome in health and disease / Nazar Reehana, Mohamed Yousuff Mohamed Imran, Nooruddin Thajuddin, Dharumadurai Dhanasekaran -- The role of probiotics and prebiotics in the composition of the gut microbiota and their influence on inflammatory bowel disease, obesity and diabetes / Rafael Resende Maldonado, Ana Lúcia Alves Caram, Daniela Soares de Oliveira, Eliana Setsuko Kamimura, Mônica Roberta Mazalli and Elizama Aguiar-Oliveira -- Skin microbiome, its impact on dermatologic diseases and intervention of probiotics / Mitesh Dwivedi, Firdosh Shah, Prashant S. Giri -- Role of dysregulation of the human oral and gastrointestinal microbiome in chronic inflammatory disease / Diana R. Cundell and Manuela Tripepi -- Microbiome in women Reproductive Health / Anchana Devi .C, Ramani Devi. T, Pavithra Amritkumar -- Crosstalk between bacteria and host immune system with special emphasis to foodborne pathogens / A.A.P. Milton, G.B. Priya, M. Angappan, S. Ghatak, V. Joshi -- Reproductive tract microbiome in animals : Physiological versus pathological condition / Vikram R., Vivek Joshi, A. P. Milton, M. H. Khan, K P Biam -- Community structures of faecal actinobacteria in Animal Gastrointestinal system / Selvanathan Latha, and Dharumadurai Dhanasekaran -- Microbiota functions in Caenorhabditis elegans / Arun Kumar , Somarani Dash and Mojibur R. Khan -- Impact of microbial communities in the female reproductive tract of bovine / M.Srinivasan, J. Helan Chandra, M.S. Murugan, C. Manikkaraja, D.Dhanasekaran, G.Archunan -- Insights into the structure, function, and dynamics of rice root and rhizosphere-associated microbiome / Ekramul Islam -- Mangrove ecosystem and microbiome / Snehal O. Kulkarni and Yogesh S. Shouche -- Role of Mycobiome in agroecosystem / Ahmed Abdul Haleem Khan -- Root nodule microbiome from actinorhizal casuarina plant / Narayanasamy Marappa, Dhanasekaran Dharumadurai and Thajuddin Nooruddin -- Growth promoting utility of plant microbiome / S.Kalaiselvi and A.Panneerselvam -- Speleothems-secondary mineral deposits microbiome / Mudgil D -- Microbiome of marine shallow water hydrothermal vents / Raju Rajasabapathy, ChellandiMohandass, A. Colaço, Rathinam Arthur James, R. Rajasabapathy and R. Arthur James -- Diversity and bioprospecting potentials of antarctic (polar) microbes / Abirami B, K. Manigundan, M. Radhakrishnan, V. Gopikrishnan, PV. Bhaskar, T. Shanmugasundaram and Syed G Dastager -- Alterations in microbial community structure and function in response to azo dyes / Sandhya Nanjani and Hareshkumar Keharia -- Soil microbiome / Govindan Nadar Rajivgandhia, Vimala RTV, Govindan Ramachandranc, Natesan Manoharanc, Wen-Jun Lia.
Includes bibliographical references and index.
Keywords: Microbial ecology; Microorganisms -- Behavior